Lexical and grammatical cohesion analysis of “nothing like us” song lyrics: written discourse analysis - Dewi, Ni Made Sinta Cahya (Yayasan Mitra Persada Nusantara, 2023)
This research aims to describe and analyze the lexical and grammatical cohesion types and identify the most common lexical and grammatical cohesion in Justin Bieber's song lyrics